The gendered effects of the Covid-19 crisis in South Africa: Evidence from NIDS-CRAM waves 1–5. Issue 5 (3rd September 2022) - Casale, Daniela; Shepherd, Debra
ABSTRACT: There is substantial evidence in the global literature that women have been disproportionately affected by the Covid-19 crisis and associated lockdowns. In this paper, we use five waves of the National Income Dynamics Study - Coronavirus Rapid Mobile Survey (NIDS-CRAM) to track the gendered effects of the pandemic in South Africa during the first year of the crisis. We focus here on the impact in the labour market and on unpaid care work in the home. We find that, relative to men, women were more severely affected in both spheres, yet they benefited less from the government income support provided to unemployed and furloughed workers. The evidence from the NIDS-CRAM survey from the first year of the pandemic therefore suggests that gender inequality in South Africa has risen, undoing some of the gains of the last two decades.